ANALISIS EFEKTIVITAS KUALITAS PELAYANAN, SOSIALISASI PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN PELAPORAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI - Upik Marsita Dewi, Suharno & Bambang Widarno (Universitas Slamet Riyadi, 2017)
The purpose of this research is to analyze the significance of the influence theeffectiveness of the quality of services, the socialization of taxation, and tax penaltiesfor compliance reporting of Annual Tax Return for individual taxpayers.Populationof the study is individual taxpayers that registered in the Services Office, Counselingand Consultation Taxation (KP2KP) Sragen. The technique of collecting datathrough interviews, observation, documentation and study questionnaires. Theresults showed that the effectiveness of the quality of services, the socialization oftaxation, and positive tax penalties and significant impact on the compliance ofindividual taxpayers in reporting their Annual Tax Return on Services Office,Counseling and Consultation Taxation (KP2KP) Sragen by the F test resultsobtained F count 31,490 with p value 0,000 < 0,05.Keywords: annual tax return, effectiveness of service quality, effective socializationof taxation, tax penalties effectiveness, compliance with individualtaxpayers.